2016
DOI: 10.1037/xlm0000177
|View full text |Cite
|
Sign up to set email alerts
|

Item strength influences source confidence and alters source memory zROC slopes.

Abstract: Increasing the number of study trials creates a crossover pattern in source memory zROC slopes; that is, the slope is either below or above 1 depending on which source receives stronger learning. This pattern can be produced if additional learning affects memory processes such as the relative contribution of recollection and familiarity to source performance. However, the pattern can also be produced by decision processes if participants are more willing to make high-confidence source judgments when they are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…A number of investigations have focused on the effects of strengthening a single source on the slope (e.g. ; repeating source A items but not source B items) of the z-transformed ROC (Starns & Ksander, 2016;Starns, Pazzaglia, Rotello, Hautus, & Macmillan, 2013;Yonelinas & Parks, 2007). However, these studies did not explore the extent to which the strength manipulation impaired memory for the items that were not strengthened, which is the focus of the list strength design.…”
Section: The Current Investigationmentioning
confidence: 99%
“…A number of investigations have focused on the effects of strengthening a single source on the slope (e.g. ; repeating source A items but not source B items) of the z-transformed ROC (Starns & Ksander, 2016;Starns, Pazzaglia, Rotello, Hautus, & Macmillan, 2013;Yonelinas & Parks, 2007). However, these studies did not explore the extent to which the strength manipulation impaired memory for the items that were not strengthened, which is the focus of the list strength design.…”
Section: The Current Investigationmentioning
confidence: 99%
“…We also note that the same occurs for postdictions of memory performance since context familiarity affects retrospective confidence judgments even when it has no impact on memory accuracy (Hanczakowski, Zawadzka, & Coote, 2014). Recently, Starns, Pazzaglia, Rotello, Hautus, and Macmillan (2013; see also Starns & Ksander, 2016) have shown that stronger memory for an item itself increases participants’ confidence in source decisions concerning the item, even though better memory that an item was presented clearly does not help answering the question about, for example, the voice in which it was presented. Together, all these results show sensitivity of metacognitive monitoring to any type of memory information elicited while making a metacognitive judgment.…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of source memory models possess the inherent feature or incorporate the post-hoc assumption that source retrieval cannot be performed for unrecognized items, the empirical findings regarding this ability are quite mixed. A number of studies have observed chance-level source accuracy for unrecognized items (Bell, Mieth, & Buchner, 2017;Malejka & Bröder, 2016;Malejka, Ciecior, Möller, & Bröder, 2018;Onyper, Zhang, & Howard, 2010;Slotnick & Dodson, 2005;Yonelinas, 1999), while others have observed above-chance accuracy for such items (Chen, Gomes, & Brainerd, 2018;Osth et al, 2018;Starns et al, 2008;Starns, Pazzaglia, Rotello, Hautus, & Macmillan, 2013;Starns & Ksander, 2016). In an attempt to make sense of this discrepancy, the following sections will provide an overview of the methodological details and empirical results of each of the aforementioned studies.…”
Section: Empirical Findingsmentioning
confidence: 99%
“…In terms of experiments that have revealed above-chance source accuracy for unrecognized items, a couple have utilized the aforementioned simultaneous design (Starns et al, 2008, Exp. 3;Starns & Ksander, 2016), while many others have utilized a blocked design (Chen et al, 2018;Osth et al, 2018;Starns et al, 2008, Exps. 1 & 2;Starns et al, 2013) that involves a block of recognition testing and a block of source testing being completed in succession (see Figure 3).…”
Section: Empirical Findingsmentioning
confidence: 99%
See 1 more Smart Citation